ANALISIS PERAN KEPEMIMPINAN REKTOR UNIVERSITAS DEHASEN BENGKULU - Handayani IS, Tuti (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2020)
Institutions such as universities are universities that organize academic and professional education in a number of disciplines of science, technology, arts and other branches of science so as to form highly complex educational institutions. To that end, the University must pay attention to how the performance of educators (Tendik) to be able to manage the course of higher education in accordance with the objectives of higher education. The leadership in the University is very important in the progress of the organization. The leadership of the University, henceforth called the Chancellor, greatly influenced the progress of the University he was leading. In Unived itself, the number of tendics that are many and have different characters will certainly give its own color in the world of Unived work environment, the work environment in Unived is inseparable from the role of a leader in this case. this is the Chancellor and his staff, Lecturers and Education. In the world of work there is no doubt there are several problems / problems that can hamper performance. Based on the formulation of the problem above, the formulation of the problem in this study is What is the role of the Chancellor's leadership at Dehasen University Bengkulu ?, with the aim of the study to determine the role of the Rector's Unived leadership. The theoretical basis used in this study is according to Henry Mintzberg (in Badeni, 2004: 2). Includes: Interpersonal Role, Decision Making and Informational Role. This research uses qualitative research with observation, interview and documentation data collection techniques. The results of the study are as follows: First, the Interpersonal Role from the research results can be seen that the Unived Rector is a leader figure and a figure responsible to his organization. Secondly, the role of the Decision Making Unived Chancellor dares to take the decision to revise the Unived Vision and Mission which includes the Entrepreneurship Vision and Mission. The Chancellor should have an entrepreneurial spirit (entrepreneur) in order to develop the company and adapt to changes in the company's environment, and dare to take decisions in order to progress the company. Third, the Role of Informational Role. From the results of the study it can be seen that the Unived Rector must ensure that the information submitted is related to the implementation of work by submitting information in accordance with their respective work